2003
DOI: 10.1210/jc.2003-030347
|View full text |Cite
|
Sign up to set email alerts
|

The Rationale and Management of Hyperglycemia for In-Patients with Cardiovascular Disease: Time for Change

Abstract: There is increasing evidence that aggressive glycemic control for patients admitted into the hospital improves clinical outcomes, especially for patients with cardiovascular disease. There appear to be a variety of mechanisms for this. Although hyperglycemia has been shown to result in poor wound healing and more infectious complications, especially after cardiac surgical procedures, what has become clear is that the treatment of hyperglycemia with i.v. glucose, insulin, and potassium (GIK) results in better c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
5

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(78 citation statements)
references
References 53 publications
0
73
0
5
Order By: Relevance
“…[25][26][27][28] Meticulous glycemic control in the hospital setting was initially reported to improve both morbidity and mortality in adults, [24][25][26][27][28] although data for youth are limited. 29 More recent studies 30,31 have not shown a reduction in mortality as a result of intensive insulin therapy.…”
Section: Insulin Pump Use In Hospitalized Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28] Meticulous glycemic control in the hospital setting was initially reported to improve both morbidity and mortality in adults, [24][25][26][27][28] although data for youth are limited. 29 More recent studies 30,31 have not shown a reduction in mortality as a result of intensive insulin therapy.…”
Section: Insulin Pump Use In Hospitalized Patientsmentioning
confidence: 99%
“…Subcutaneous protocols have also been developed that may have value in specific circumstances. 26,27 What then is the role of insulin pump use and subcutaneous insulin administration in youth with T1D who are hospitalized? We have previously advocated for people with T1D being allowed to continue to use their insulin pumps for elective and non-acute hospitalizations.…”
Section: Insulin Pump Use In Hospitalized Patientsmentioning
confidence: 99%
“…Strict glycemic control has been demonstrated to be beneficial in other settings as well, with intravenous insulin in preference to the subcutaneous route in many clinical situations, including diabetic ketoacidosis and the nonketotic hyperosmolar state (2), critical care illness (1), myocardial infarction or cardiogenic shock (3)(4)(5), and the postoperative period after cardiac surgical procedures (6). Other indications for intravenous insulin infusion therapy include use in patients with diabetes who are receiving nothing by mouth, general perioperative care, total parental nutrition, or high-dose corticosteroid therapy; in patients who have had a stroke; in women during labor and delivery; as a dose-finding strategy in anticipation of initiation of subcutaneous insulin; and in prevention or treatment of infection.…”
mentioning
confidence: 99%
“…For patients in intensive care units, the most appropriate management would be the initiation of an intravenous insulin drip with frequent monitoring and titration of the insulin dose (36,37). Many insulin infusion protocols are currently used.…”
Section: Patients With Type 1 Diabetesmentioning
confidence: 99%
“…The total insulin requirement for a patient with type 2 diabetes is estimated to be 0.6 U/kg (36,37). Approximately half of the total dose will be basal longacting or intermediate-acting insulin, and one sixth of the total dose (0.1 U/kg per meal) will be rapid-acting insulin administered before meals.…”
Section: Reviewmentioning
confidence: 99%